HERPETOFAUNA SPECIES DIVERSITY AT OIL PALM PLANTATIONS IN MOROWALI REGENCY, CENTRAL SULAWESI - Sitti Ramlah; Lukman Nadjamuddin; Andi Chairil Ichsan (Jurnal Belantara, 2026)
Central Sulawesi is one of Indonesia’s oil palm producing provinces, with a plantation area of 60,913.77 ha distributed across nine districts, including Morowali Regency. Various allegations that oil palm plantations are associated with a decline in biodiversity, particularly herpetofauna, have encouraged research on herpetofauna and mammals. This study aimed to determine the diversity of herpetofauna species in oil palm plantations in Morowali Regency at Ungkaya Village. The research sites included old oil palm plantations, young oil palm plantations, and areas with High Conservation Value (HCV). The distance between the old oil palm plantations and the young oil palm plantations was approximately ±4 km, while the distance from the old oil palm plantations to the HCV area was ±3 km, and from the young oil palm plantations to the HCV area was ±5 km. Data collection was conducted using the Visual Encounter Survey (VES) method combined with a 1 km transect at each land cover age. Observations were carried out between 19:00 and 21:00 WITA. The results showed that changes in land cover within oil palm plantations did not cause a reduction in the number of herpetofauna species. A total of 13 reptile and amphibian species were recorded across all land cover types. The species diversity and richness indices indicated moderate values (H′ = 2.32 and R = 2.47), suggesting that oil palm plantations can function as habitats for herpetofauna. The species evenness index value of 0.91 indicates that herpetofauna are able to inhabit oil palm plantations across all land cover ages.